DIFFERENTIAL REDOX AND SORPTION OF CR(III/VI) ON NATURAL SILICATE AND OXIDE MINERALS: EXAFS AND XANES RESULTS - Peterson M.L.; Brown G.E.; Parks G.A.; Stein C.L. (My University, 1997)
Synchrotron-based X-ray absorption fine structure (XAFS) spectroscopy was used to investigate the reduction of aqueous Cr(VI) to Cr(III) in magnetite-bearing soils from Cr-contaminated sites. Soils from two field sites were examined, showing that mixed-valence Cr(III/VI) effluent is reduced to Cr(III) when associated with the magnetite fraction of the soil, whereas the Cr effluent associated with non-Fe(II)-bearing minerals results in mixed Cr(III/VI) adsorbates or precipitated phases. The Fe2+ in magnetite, Fe2+Fe3+2O4, may act as an electron source for heterogeneous Cr(VI)-to-Cr(III) reduction, converting magnetite topotactically to maghemite, γ-Fe3+2O3. The ratio of Cr(VI)/total Cr was determined by the height of the Cr(VI) XAFS pre-edge feature, which is due to a 1s to 3d electronic transition. This pre-edge feature was calibrated as a function of Cr(VI)/Cr(III) using mixtures of Cr(III) and Cr(VI) model compounds. Environmental remediation of Cr-contaminated sites requires knowledge of chromium oxidation and speciation, and XAFS spectroscopy may be used to supply both types of information with minimal sample processing or data analysis.